Associations between work-related variables and workplace violence among Chinese medical staff: A comparison between physical and verbal violence - Sun, Long; Zhang, Wen; Cao, Aihua (Frontiers in Public Health, 2023)
Background: Workplace violence (WPV) against medical staff had been an important public health and societal problem worldwide. Although lots of studies had implied the differences between physical violence (PV) and verbal violence (VV) against medical staff, less studies were conducted to analyze the different associations between work-related variables, PV, and VV, especially in China. Methods: A cross-sectional study was conducted among Chinese medical staff in public hospitals, and 3426 medical staff were interviewed and analyzed. WPV, including PV and VV were evaluated by medical staff’s self-report. Work-related variables, physical disease, depression, and social-demographic variables were also measured. The work-related variables included types of medical staff, professional title, hospital level, manager, working years, job changing, working hours/week, night duty times/week, monthly income, self-reported working environment, and social position. Logistic regressions were conducted to examine the factors associated with PV and VV. Results: There were 489 medical staff (23.0%) reported the experience of PV, and 1744 ones (50.9%) reported the experience of VV. Several work-related variables was associated with PV and VV, including nurse (OR=0.56 for PV, p<0.01; OR=0.76 for VV, p<0.05), manager (OR=1.86 for PV, p<0.01; OR=1.56 for VV, p<0.001), night duty frequency/week (OR=1.06 for PV, p<0.01; OR=1.03 for VV, p<0.01), bad working environment (OR=2.73 for PV, p<0.001; OR=3.52 for VV, p<0.001), averaged working environment (OR=1.51 for PV, P<0.05; OR=1.55 for VV, p<0.001), bad social position (OR=4.21 for PV, P<0.001; OR=3.32 for VV, p<0.001). Working years (OR=1.02, p<0.05), job changing (OR=1.33, p<0.05), and L2 income level (OR=1.33, p<0.01) were positively associated with VV, but the associations were not supported for PV (all p>0.05). The other associated factors were male (OR=1.97 for PV, P<0.001; OR=1.28 for VV, p<0.05), depression (OR=1.05 for PV, P<0.001; OR=1.04 for VV, p<0.001). Conclusion: Both PV and VV were positively associated with work-relative variables, such as doctor, manager, more night duty frequency, perceived bad working environment or social position. There were also some variables, which were only associated with VV, such as working years, job changing, and monthly income. Some special strategies about the work-related variables should be applied for controlling PV and VV.